Like a Mighty Army [compact disc, unabridged] - Weber, David, 1952- (Weber, David, 1952- Safehold series., 2013)
Merlyn Athrawes is the cybernetic avatar of a warrior a thousand years dead, felled in the war in which Earth was lost. Merlyn has one purpose: to restart the history of the long-hidden human race. The island empire of Charis has declared its independence from the fraudulent alien Church, and with Merlyn's help has vaulted into a new age of steam-powered efficiency. But the wounded Church is regrouping. Its armies and resources are vast. The fight for humanity's future isn't over.